Efectividad de las terapias de tercera generación en los trastornos de la personalidad. - Cárdenas Vallejo, Pamela Anneleese (2024)
The present research project was based on a bibliographic review aimed at determining the effectiveness of third-generation therapies in personality disorders. This study employs a bibliographic and descriptive approach. The methodological process involved an exhaustive search of various information sources, with a population of 501 scientific articles chosen according to predefined variables. Through inclusion criteria and methodological quality assessment (CRF-QS), a filtration and selection process resulted in a non-probabilistic sample of 40 articles. The findings indicate that the most effective third-generation therapies were dialectical behavioral therapy and acceptance and commitment therapy for treating individuals with personality disorders, particularly those of borderline, antisocial, and histrionic types, thereby reducing symptoms and enhancing their quality of life.